A reziliens működés kompetenciáinak fejlesztési lehetőségei „a hivatásgondozó” – szupervíziós – munkában segítőknél, különösen a lelkipásztori hivatásban - BECSKY, Borbála (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2022)
Opportunities for the Development of the Competences of Resilient Operation in the Professional Care – Supervision Work – of Helpers, Especially in the Pastoral Vocation. Within the framework of this study, I present the specific resilience-enhancing role and characteristics of helpers, of a professional life path, profes-sional caregivers, and supervising work with special focus on pastoral work, and helper vocation. I examine how the pastoral vocation picture finds its place in the family of helping vocations, how it can be defined in the search for identification, how therapy, education, how professional care appear in almost every aspect of pasto-ral work, and how vocation care and super success can be adapted in pastoral work. In each chapter, my reflection covers the most important resilience issues, identity issues, the person-centered approach and related concepts. I examine the relationships and methodology of resilience and supervision within the framework of helping occupations in the process of becoming a child, and I dis-cuss how learning appears in the course of professional care along the lines of the ministry. The development of resilient competences in professional care has become important since the regime change, especially in the pastoral profession and in the intertwining of cooperation with assisting professions. Regarding the dia-logue, purity and authentic presence of helper vocations and roles, the transpar-ency and pastoral psychological approach of contexts and systems is an increas-ingly topical direction and issue. Main question: Is there sufficient insight and awareness to examine the re-spective helping vocations, the pastor's professional life path, his tired or burnt-out personality in the ministry, and his important fighting ability in the midst of crises? Are we looking for preventive ways? Is today’s pastor motivated enough to pay attention to his psychical, spiritual, physical, and social health? If so, how can these be achieved? As a researcher, as an active psychotherapist working with couples and fami-lies, as a professional/supervisor, pastor wife, active Christian pastoral and men-tal health professional, and a pastoral psychologist, I think in several dimensions and systemic perspectives. As a helper, professional care-giver/supervisor, the issue of identity is im-portant. I see spirituality as a kind of “driver” in the process, and I think it is decisive – it can be inspiring, but it can also be disincentive. Calibration is the task of the authentic helper of the time. That is, continuous reflection and self-reflection in a spiritual dimension. The goal is to mature, to fight/cope resilient-ly. The freedom to jump, the intuitive way, the path of development and learn-ing are puzzle pieces of the spiritual dimension, a space for coping and fulfil-ment. Knowing God, I know myself, and knowing myself (in humility) brings me closer to God.